Effect of Variations and Types of Filler on Compressive Strength and Density of CLC Light Bricks - Dwi Pangga; Dwi Sabda Budi Prasetya; Habibi (International Journal of Science, Technology & Management, 2020)
Abstract. In the process of producing light brick, there is ‘mixed foam’ agent to reduce the value of its density, therefore it can reduce the values of compressive strength. To reduce its density and increase the value of pressure, the variations and types of fillers must match the composition. The manufacture of light brick type CLC (Cellular Lightweight Concrete) has been carried out with several variations and types of fillers to compare the values ??of compressive strength and density. The fillers are as follows: Water Hyacinth, Banana Midrib, and Wood Shavings based on gold processing waste (GPW). The compressive strength and density test results on various filler percentages are as follows: 1). Water hyacinth at the percentage of 0%, 15%, 30%, 45%, 60% has compressive strength: (2.43; 0.73; 0.69; 0.59; 0.65) MPa while the densities are ( 1.62; 1.20; 1.41; 1.13; 1.20) gr / cm3. 2). Banana midrib with variations are: 0-4 midribs has compressive strength: (2.43; 1.25; 1.68; 2.13; 1.32) MPa and its densities are (1.62; 1.29; 1.12; 1.16; 1.25) gr / cm3. 3). Wood shavings with percentage: 0%, 25%, 50%, 75% have compressive strength: (2.43; 1.39; 2.04; 1.72) MPa and their densities: (1.62; 1, 21; 1.26; 1.20) gr / cm3. The results showed that the best compressive strength was produced by the filler from wood shavings with an average of 1.85 MPa and a density of 1.31 gr / cm3. The lowest density was obtained from the banana midrib filler which was 1.29 gr / cm3 with a compressive strength of 1.76 MPa. It can be concluded that light brick is best suited to wood shavings fillers.